Motor abilities and morphological characteristics of competitive boxers and recreational boxers - Stankovic, O.; Grubješic, M. (Sport Science & Practice, 2020)
When it comes to a sport such as boxing, motor abilities are often in significant correlation with the morphological status of a competitive or recreational boxer. All the factors that affect the result of motor abilities in boxing are directed, in great deal, towards morphological status (with an aspiration to achieve an idea boxing category in case of competitive boxers). The main aim of this research was to examine the differences in the motor abilities and morphological characteristics between competitive boxers and recreational boxers. The sample of respondents consisted of 10 senior boxers from the BC `Crvena Zvezda`. The assessment of motor abilities of competitive boxers and recreational boxers was made using five tests from the Eurofit battery of tests and with one test for coordination assessment. Data were processed by means of descriptive statistical analysis, as well as the Mann Whitney U test which was used to test the difference of group respondents on the level of statistical significance p<0.05. The results of this research showed that competitive boxers achieved significantly better results on three out of six tests for the assessment of motor abilities. When it comes to morphological characteristics of competitive boxers and recreational boxers, there were no significant differences. The results of the research show that more intense boxing training contributes to better manifestation of certain motor skills.